Pengaruh Cekaman Salinitas Terhadap Pertumbuhan Dan Perkembangan Bandotan (Ageratum conyzoides L.) - Bahrul Ulum, Fuad; M. Akbar, Salahuddin; Andiana, Jocelin; Rosyadi, Achmad; Setyati, Dwi (Journal of Natural Sciences, 2023)
Salinity stress enhances plants' growth and development, leading to decreased productivity. Ageratum conyzoides L., also known as Bandotan, is an invasive plant that has spread throughout almost all regions in Indonesia. Investigating the adaptation mechanisms of this plant offered insights into the stress tolerance levels to the salininty and was important for the mitigation of the consequences of its invasivenessnature. The objective of this research was to investigate the impact of salinity stress on the growth and development of A. conyzoides.  The study was carried out in a greenhouse between April and May 2022. The plants were grown under two degrees of salinity stress (i.e., 2000 ppm for moderate stress, and 75000 ppm for extreme stress). The results indicated that A. conyzoides was adaptive to moderate salinity conditions. In extreme stress conditions, A. conyzoides expressed stress by decreasing the plant height and total stomata. The plant adapted by developing flowers at a faster rate as a defense mechanism for the propagation of future generations.